Порівняння backend та frontend тестування у веб-застосунках - Прокоп’єв, С. А. (ХНУРЕ, 2024)
This work is devoted to comparing backend and frontend testing, analysing their strong and weak sides, their use in ensuring the comprehensive test coverage of the product. The focus will be on both manual and automation aspects of testing and how we can make sure that the critical functionality works as expected to provide the best user experience and not harm firm’s reputation and business operations. As an example, the checkout charging process will be discussed as a part of this work
Keywords: backend тестування; frontend тестування